Evaluation of the Quality of Midwifery Care Based on Continuity of Care for Pregnant Adolescents in Central Lombok: Qualitative Study - Supiana, Nia; Mutianingsih, Rosa; Mawaddah, Shohipatul; Daniyati, Asri; Safinatunnaja, Bq (Yayasan Ahmad Mansyur Nasirah, 2025)
Adolescents who experience pregnancy are a vulnerable group in accessing reproductive health services. The implementation of continuous midwifery services or Continuity of Care (CoC) is believed to be able to improve the quality of services, but so far, its implementation in adolescent groups has not been widely studied. This research aims to explore perceptions, experiences and identify factors that support and hinder the implementation of CoC-based midwifery services. This study uses a qualitative design with a phenomenological approach. The research locations were in two Community Health Centers in the Central Lombok region, namely work areas that have a high prevalence of teenage pregnancy rates, namely the Sengkol and Batu Jangkih Community Health Centers. Involving 12 teenagers at various stages of pregnancy and 1 head of community health center, as well as 5 midwives implementing the CoC program. Purposive sampling technique was used to select informants. Data collection was carried out through in-depth interviews using semi-structured guidelines, observation of service interactions, and review of service documents conducted over 2 months. Data validity is strengthened by source triangulation and member checking. Data were analyzed using a thematic approach. The research results show that the CoC is implemented consistently and builds adolescent trust through ongoing relationships with midwives, however the quality of service is not optimal due to limited staff, lack of psychosocial approach, stigma, low health literacy, as well as transportation and economic barriers. To increase the effectiveness of the CoC, it is necessary to strengthen the service system and cross-sector support and requires in-depth studies for future researchers regarding the involvement of adolescents in the medical decision-making process, the impact of using digital technology, the relationship between socio-economic factors and the implementation of CoC, and comparing the implementation of CoC in rural areas with urban areas.